Selective efferent vagal stimulation in heart failure - Lindsea C. Booth; Baagavi Saseetharan; Clive N. May; Song T. Yao (Experimental Physiology)
Abstract Patients diagnosed with heart failure have high rates of mortality and morbidity. Based on promising preclinical studies, vagal nerve stimulation has been trialled in these patients using whole nerve electrical stimulation, but the results have been mixed. This is, at least in part, due to an inability to selectively recruit the activity of specific fibres within the vagus with whole nerve electrical stimulation, as well as not knowing which the ‘therapeutic’ fibres are. This symposium review focuses on a population of cardiac‐projecting efferent vagal fibres with cell bodies located within the dorsal motor nucleus of the vagus nerve and a new method of selectively targeting these projections as a potential treatment in heart failure.